Comparison of Energy Output of Multi-Angle Positioned Windmill Propeller Blades - John S. Lanuza, Elymer; C. Pacis, Michael; Vincent Santiago, Ronald; S. Vallestero II, Gorgonio (International Journal of Engineering and Technology, 2018)
Electrical energy is one of the basic things that humans need to survive. As the earthâ€™s population grows and the number of technology that utilize electricity increases, the earthâ€™s supply of fossil fuels and other limited energy sources are fast depleting. Electrical energy is a critical element of almost everything that affects humanâ€™s daily routine. That is why most Filipinos expect theÂ aid of electrical energy to improve their lives, and are aware that in each usage, unforeseen energy expense reduces the funds intended for other needs orÂ necessities. Along with these principles, windmill is one of the options the Philippines is now trying to tap. Based on past studies, there are many types of windmills. Most of them have horizontal or vertical shaft. A horizontal shaft is level to the ground or pointing straight parallel with the ground. A vertical shaft on the other hand is upright or a little bit tilted in perpendicular alignment with the ground. A similar study was done showing that at 0 degree there was no amp or energy produced. At 15 degrees there was also no ammeter reading forÂ energy produced.Â TheÂ reading at 30 degrees was the first blade pitch to produce a reading on the ammeter. The 30 degree blade pitch produced 6 amps of energy. The 45 degree blade pitch produced a reading on the ammeter of 12Â amps ofÂ electric power.Â The 60 degree blade pitch produced theÂ highest reading on the ammeter. It generated 15 amps of energy. A reading of 10 amps was produced from the 75 degree blade pitch. At 90 degrees no energy was produced on the ammeter.Â Â Â